The Mission - Ghia, Fernando (Viva Video, 2003)
Based on historical events that occurred around the borderlands of Argentina, Paraguay and Brazil in the year 1750, the drama concerns two men, a priest and a soldier, who unite to shield a South American Indian tribe from brutal subjugation by 18th century colonial empires.